2015
DOI: 10.1016/j.physrep.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of local structure in dynamical arrest

Abstract: Amorphous solids, or glasses, are distinguished from crystalline solids by their lack of long-range structural order. At the level of two-body structural correlations, glassformers show no qualitative change upon vitrifying from a supercooled liquid. Nonetheless the dynamical properties of a glass are so much slower that it appears to take on the properties of a solid. While many theories of the glass transition focus on dynamical quantities, a solid's resistance to flow is often viewed as a consequence of its… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
457
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 406 publications
(483 citation statements)
references
References 564 publications
(1,149 reference statements)
22
457
3
1
Order By: Relevance
“…18 At higher temperatures, there is an increase in both the atomic displacements and the number of atoms participating in the jumps. 21 It is pertinent to note that, although crystallisation is universally known to be a first-order thermodynamic transformation, 22,23 glass transition has been prevailingly considered as a largely dynamical phenomenon 24 and soft phonons are known to be related to the dynamics of amorphous alloys. 18,25 Although the energy landscape curvature and mean-squared atomic displacements (MSD) are two different quantities, they are inter-connected often in complicated relations.…”
Section: Resultsmentioning
confidence: 99%
“…18 At higher temperatures, there is an increase in both the atomic displacements and the number of atoms participating in the jumps. 21 It is pertinent to note that, although crystallisation is universally known to be a first-order thermodynamic transformation, 22,23 glass transition has been prevailingly considered as a largely dynamical phenomenon 24 and soft phonons are known to be related to the dynamics of amorphous alloys. 18,25 Although the energy landscape curvature and mean-squared atomic displacements (MSD) are two different quantities, they are inter-connected often in complicated relations.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown instead that the supercooled state contains a lot of structural order aside from crystalline order [34,35]. For hard spheres, for example, the competition between crystalline order and icosahedral (or five-fold symmetric) order plays a big role in the nucleation process, and on its avoidance [12,17,18,44,[54][55][56][57]. For systems with a metastable critical point, e.g.…”
Section: Extending Classical Nucleation Theorymentioning
confidence: 99%
“…There is a long tradition in the theory of glasses of attributing glass behavior to the growth of particular types of structural order, such as icosahedral order in three dimensions [17][18][19]. Recent work by Cubuk et al [20] on the flow of jammed and glassy systems under stress has shown that regions that are susceptible to rearrangement can be discovered by machine-learning methods that combine information derived from several features of the local structure, such as the radial distribution of particles and the bond angles.…”
Section: Introductionmentioning
confidence: 99%